Effective learning and teaching in social policy and social work - Burgess, Hilary, 1954-; Taylor, Imogen (London ; New York : RoutledgeFalmer, 2005)
Written to meet the needs of teachers, lecturers and tutors working at different levels and in many situations, this is the guide to understanding the key issues, best practices and new developments in social work and social policy.
Dancing on a moving carpet : the changing context / Pat Young and Hilary Burgess -- Designing the curriculum : complexity, coherence and innovation / Hilary Burgess and Zoë Irving -- Participation in social policy and social work learning / Peter Beresford -- Promoting equality and inclusion / Bill Beaumont and Sarah Cemlyn -- Students learning to learn / Viviene E. Cree -- Promoting interactive learning and teaching / Hilary Burgess and Pat Young -- Walking the assessment tightrope / Beth R. Crisp and Pam Green Lister -- Towards eLearning : opportunities and challenges / Jackie Rafferty, Melanie Ashford and Sue Orton -- Developing learning beyond the campus : increasing vocationalism and declining pedagogy? / Duncan Scott and Steven M. Shardlow -- Interprofessional education / Melanie Ashford and Judith Thomas -- Continuing professional development and education / Pat Higham and Bob Rotheram -- Globalization : implications for learning and teaching / Zoë Irving and Malcolm Payne -- International perspectives / Karen Lyons -- Developing the university as a learning organization / Imogen Taylor.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Social policy -- Study and teaching (Higher); Human services -- Study and teaching (Higher); Social work education; Service social -- Étude et enseignement; POLITICAL SCIENCE -- Public Policy -- Social Policy; Social work education; Social policy -- Study and teaching (Higher); Human services -- Study and teaching (Higher); Human services -- Study and teaching (Higher); Social policy -- Study and teaching (Higher); Social work education